Inventory Control Systems for Deteriorating Items Considering Carbon Emissions: A Theoretical Overview (International Journal of Scientific Research in Science and Technology, 2025)
The need for sustainable inventory management has become critical as businesses aim to minimize both costs and environmental impact. Managing deteriorating items—perishable goods, chemicals, or products with limited shelf lives—introduces unique challenges, as stock levels must be carefully balanced to avoid waste. Traditionally, inventory models focused on cost reduction without considering carbon emissions generated during production, storage, and disposal. However, as regulatory and societal pressures grow, companies are increasingly integrating carbon-sensitive strategies into inventory management. This paper examines theoretical models of inventory control for deteriorating items, focusing on how carbon emissions are incorporated to achieve a balance between operational efficiency and environmental responsibility.